Influence of age at disease onset on future relapses and disability progression in patients with multiple sclerosis on immunomodulatory treatment. (3rd April 2020) - von Wyl, V.; Décard, B. F.; Benkert, P.; Lorscheider, J.; Hänni, P.; Lienert, C.; Kuhle, J.; Derfuss, T.; Kappos, L.; Yaldizli, Ö.
Abstract : Background and purpose: To investigate the relation of age at disease onset and clinical outcomes across the lifespan from adolescence in patients with multiple sclerosis (MS) on disease‐modifying therapy (DMT). Methods: We analysed data from the Swiss Association for Joint Tasks of Health Insurers database containing data from 14 718 patients with MS. Patients were included in this analysis when they were on DMT for at least 1 year. The influence of age at disease onset on future relapses and disability worsening was explored using multivariable Cox proportional hazard regression models. Results: Data from 9705 patients with MS were analysed. Pediatric‐onset MS patients ( n = 236) had higher relapse rates and marginally slower disability worsening rates compared with adult‐onset MS ( n = 9469). The risk of relapses was highest in childhood and decreased continuously to about 35 years of age. It remained stable for about a decade and then again continuously decreased. In contrast, disability worsening hazards remained stable from childhood to about 32 years of age and then increased sharply around the age of 45 years. Conclusions: Age is an important factor independently affecting clinical outcomes in MS. This should be considered when designing clinical trials or choosing DMT.